2018
DOI: 10.1371/journal.pone.0200519
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal nutritional supplementation in conjunction with a breastfeeding support program during the last trimester to 12 weeks postpartum on breastfeeding practices and child development at 30 months old

Abstract: BackgroundMaternal nutrition during pregnancy and breastfeeding is important for the healthy growth and development of the fetus and infant.PurposeThis study aimed to evaluate the long-term effects of a maternal milk supplementation (MMS) in conjunction with a breastfeeding support program on breastfeeding practices including duration of any breastfeeding and exclusive breastfeeding and child neurodevelopment outcomes at 30 months old.MethodsWe followed up the offspring of 204 Vietnamese women who completed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
1
9
0
1
Order By: Relevance
“…Lactation leading to increased nutrient demands and modest improvements in maternal BMI, MUAC, and hemoglobin concentrations in mothers in the intervention group call for focused nutritional programs for lactating mothers. A higher proportion of exclusive breastfeeding due to maternal supplementation has also been shown in previous randomized controlled trials ( 41 , 42 ). One of the common reasons for introducing food other than breast milk to low-middle-income settings is the perception of inadequate maternal milk production ( 43 – 45 ).…”
Section: Discussionsupporting
confidence: 72%
“…Lactation leading to increased nutrient demands and modest improvements in maternal BMI, MUAC, and hemoglobin concentrations in mothers in the intervention group call for focused nutritional programs for lactating mothers. A higher proportion of exclusive breastfeeding due to maternal supplementation has also been shown in previous randomized controlled trials ( 41 , 42 ). One of the common reasons for introducing food other than breast milk to low-middle-income settings is the perception of inadequate maternal milk production ( 43 – 45 ).…”
Section: Discussionsupporting
confidence: 72%
“…We calculated pooled effect sizes if at least five studies reported an intervention versus control group comparison in any category of intervention (eg, nutritional supplementation and promotion of responsive care and learning opportunities). We applied the same criterion to stratified 29 Ong et al 37 Jeon et al 41 Lind et al 31 Rosado et al 15 Oelofse et al 52 Nahar et al 48 Smuts et al 62 Husaini et al 50 Phuka et al 21 Maleta et al 17 Krebs et al 54 Bauserman et al 55 Faber et al 14 Hess et al 16 Dewey et al 20 77 Luby et al 23 Stewart et al 22 Gladstone et al 61 Lees et al 80 Hallamaa et al 82 Tomlinson et al 78 Tumwine et al 79 Dewey et al 20 Adu-Afarwuah et al 18 Ashorn et al 19 Zhang et al 59 Thomas et al 60 Gowachirapant et al 51 Hamadani et al 35 Jacobson et al 58 Schmidt et al 53 Hanieh 36 Zhu et al 56 Nguyen et al 34 Christian et al 40 Gonzalez-Casano 87 Tofail et al 49 In utero 3 6 9 12 15 18 Months Years 64 Nahar et al 48 Hamadani et al 70 Tofail et al…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Furthermore, salient underlying theoretical mechanisms linking maternal mental health difficulties and infant development should also be considered. Namely, breastfeeding is one of the most important co-occupations between mother and infant and has been linked to short-term and long-term offspring health (e.g., chronic disease risk across the lifespan) [ 13 ] and developmental outcomes (e.g., IQ, attention and other cognitive skills, motor, and socioemotional domains) [ 14 ]. Co-occupation has been defined in the literature as the give-and-take between caregivers and infants engaged in a mutual task, such as feeding, including shared physicality, emotionality, and intentionality [ 15 ].…”
Section: Introductionmentioning
confidence: 99%